Sistem Informasi Akuntansi untuk Usaha Mikro, Kecil, dan Menengah (UMKM) Bidang Jasa di Indonesia - Dyah Sulistyowati Rahayu (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Micro, small, and medium enterprises (MSMEs) is a form of business which is stipulated in Law No.20 of 2008 where the amount is very dominant in Indonesia. One of the obstacles in developing MSMEs is the limited access to funds. One of which is caused by the absence of financial statements based on the Accounting Standards for Entities Without Public Accountability (SAK-ETAP). MSMEs also experienced a shortage of human resources, especially in technology and accounting. To overcome this and to lead a good corporate governance, we need an accounting information system for MSMEs. This research resulted the accounting information system for MSMEs based on SAK-ETAP and has a general nature so that it can be applied to business in service sector with minor adjustments. This research resulted the complete information system as well as the UML design. The study also attached the complete mapping of each type of transactions to the financial statements. By using this information system, the MSME’s especially in service sector could generate the financial statement, order, invoice, and other report automatically